Feasibility of preparing of silicon nitride ceramics components by aqueous tape casting in combination with laminated object manufacturing. (5th February 2015) - Liu, Shichao; Ye, Feng; Liu, Limeng; Liu, Qiang
Highlights: Aqueous tape casting was employed to fabricate silicon nitride green tapes. Complex shaped Si3 N4 components were prepared by laminated object manufacturing process. Si3 N4 components with complex shapes possessed good strength (∼475 MPa). High density of Si3 N4 components with complex shapes was observed (∼94.3%). Abstract: Homogeneous green silicon nitride sheets consisting of 48.7 vol.% ceramic particles were prepared by tape casting. The slurry, used to prepared green tapes, own obvious shear-thinning behavior. No noticeable precipitation during tape casting process was found revealed by the result of energy dispersion spectrum analysis. Components with complex shapes were fabricated by stacking layer by layer of the green sheets and a subsequent pressureless sintering at 1800 °C for 1 h. All α-Si3 N4 has transformed into β-Si3 N4 indicated by the result of X-ray diffraction. Due to the high homogeneous packing of the ceramic particles in the green bodies, the ceramic components could be sintered to full density with no noticeable distortions. Good flexural strength for the ceramic samples was observed.